2019
DOI: 10.2147/ijn.s184792
|View full text |Cite
|
Sign up to set email alerts
|

<p>The in vitro and in vivo anti-melanoma effects of hydroxyapatite nanoparticles: influences of material factors</p>

Abstract: Background Treatment for melanoma is a challenging clinical problem, and some new strategies are worth exploring. Purpose The objective of this study was to investigate the in vitro and in vivo anti-melanoma effects of hydroxyapatite nanoparticles (HANPs) and discuss the involved material factors. Materials and methods Five types of HANPs, ie, HA-A, HA-B, HA-C, HA-D, and HA-E, were prepared by wet chemical method combining with polymer templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 62 publications
(101 reference statements)
3
32
0
Order By: Relevance
“…These findings suggest that nHA not only induces osteogenesis to repair hard tissue injury but also promotes selective apoptosis of tumor cells. Thus, nHA has emerged as an ideal candidate for biomedical applications 18,19. However, it is difficult to endow CaP ceramics with both an interconnected porous structure and a bioactive nanostructured surface, as grains grow rapidly and pores collapse easily during the sintering process 1.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that nHA not only induces osteogenesis to repair hard tissue injury but also promotes selective apoptosis of tumor cells. Thus, nHA has emerged as an ideal candidate for biomedical applications 18,19. However, it is difficult to endow CaP ceramics with both an interconnected porous structure and a bioactive nanostructured surface, as grains grow rapidly and pores collapse easily during the sintering process 1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the HAp-S with the diameter of 1.926 nm was used in the following calculations. On the other hand, changes of the nanoparticles’ geometrical parameters, such as the Ca:P ratio or the aspect ratio, may lead to variable net-charge and the electrostatic potential surface ( Supplementary Figure S1 ), though it was reported that the zeta potentials of HAp nanoparticles of various shape that have been characterized in experiments are all negative ( Wu et al, 2019 ); besides, changes in the size may also lead to a change in the geometric matching of the interface between the two. Therefore, we will focus on the interactions between the fixed-size nanoparticles ( Figure 1C,D ) and the protein in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, HAp-S leads to a more significant conformational change on AP2-μ2 than that of HAp-N. In literature, it was reported that the sphere-shaped HAp nanoparticles effectively inhibited the growth of A375 melanoma cells (34.90% viability); in contrast, the rod or needle-like HAp nanoparticles moderately affected the viabilities of melanoma cells (60.43%–74.90%) ( Wu et al, 2019 ). Presumably, HAp-S is likely to facilitate its transportation in the cellular environment by shifting AP2-μ2 to a locked conformation, and therefore resulting in a more profound tumor-suppressive effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the zeta potential values measured by different research groups may be different from each other, the experimental data of various nanoparticles collected in Table 1 could still give some general trends, especially for the potential of binding with the biological moelcules. As shown in Table 1, the HA nanoparticles with different morphologies, 14 Ag@HA, 30 F-Cl@HA, 31 and Au/Ag@ HA, 35 had negative zeta potentials, some of which were found to be efficiently taken up by A375 cells and MG-63 cells. The HA particles with several kinds of oxygencontaining addtives, such as, citric acid@HA, 32 oxalic acid@HA 33 and malic acid@HA 34 also exhibited negative zeta potentials, whose values were dependent on the pH values (Table 1), Similar to HA nanoparticles, some other nanoparticles including Au/Ag nanoparticles, 35 cerium oxide nanoparticles 76 and iron oxide nanoparticles 29 with negative zeta potentials were able to effectively absorbed on MG-63, A549, and HeLa cells.…”
Section: High-throughput Experimentations (Hte) Of Cap Clustering Processesmentioning
confidence: 99%